Bitumen Filler System for Different Grades of Bitumen - Ruzaidi Bin Ab. Aziz, Ruzaidi (Universiti Teknologi Petronas, 2010)
The aim of the paper was to improve knowledge on the bitumen mixture, as well as investigating the numerical quantity relationship between the structures of fillers and the bitumen. In bituminous mixture the finer fraction of the filler have the highest surface area or specific surface.